2020
DOI: 10.5802/ahl.40
|View full text |Cite
|
Sign up to set email alerts
|

On the convergence of smooth solutions from Boltzmann to Navier–Stokes

Abstract: In this work, we are interested in the link between strong solutions of the Boltzmann and the Navier-Stokes equations. To justify this connection, our main idea is to use information on the limit system (for instance the fact that the Navier-Stokes equations are globally wellposed in two space dimensions or when the initial data is small). In particular we prove that the life span of the solutions to the rescaled Boltzmann equation is bounded from below by that of the Navier-Stokes system. We deal with general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 39 publications
(37 reference statements)
1
44
0
Order By: Relevance
“…S ε (t) := exp(t(L − εv • ∇ x )), construct smooth solutions in L ∞ v H s x M −1/2 1 + |v| k with s > d/2, and prove their convergence as ε goes to zero. In [15], the authors prove a converse result in the same functional space ; as long as a solution f 0 to the incompressible Navier-Stokes-Fourier system exists, a solution f ε to (2) exists for ε small enough and f ε converges to f 0 . Both papers rely on the spectral study led by [13,33] of the inhomogeneous linearized Boltzmann operator in L 2 v H s x M −1/2 which dictates the asymptotic of S ε and ε −1 S ε Q.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…S ε (t) := exp(t(L − εv • ∇ x )), construct smooth solutions in L ∞ v H s x M −1/2 1 + |v| k with s > d/2, and prove their convergence as ε goes to zero. In [15], the authors prove a converse result in the same functional space ; as long as a solution f 0 to the incompressible Navier-Stokes-Fourier system exists, a solution f ε to (2) exists for ε small enough and f ε converges to f 0 . Both papers rely on the spectral study led by [13,33] of the inhomogeneous linearized Boltzmann operator in L 2 v H s x M −1/2 which dictates the asymptotic of S ε and ε −1 S ε Q.…”
Section: Introductionmentioning
confidence: 94%
“…The theory of hydrodynamic limits for smooth solutions of the Boltzmann equation was partially extended to a larger class of Sobolev spaces with polynomial weights during the last decade: a Cauchy theory close to equilibrium was developped in [19] and their weak compacity with respect to ε was shown in [10]. The strong convergence could not be deduced as in [8,15] since the spectral decomposition from [13] was not known to hold in the case of polynomial weights. This paper aims at providing such a generalization.…”
Section: Introductionmentioning
confidence: 99%
“…This is made possible by adapting the strategy from [7] of writing the solution to the Boltzmann equation as the sum a part with polynomial decay and a second one with Gaussian decay. The Gaussian part is treated with an approach reminiscent of the one from [17].…”
mentioning
confidence: 99%
“…In [17], I. Gallagher and I. Tristani improved this fixed point approach by considering the equation satisfies by f ε −f 0 , where f 0 is known to exist thanks to Theorem 2. This allowed to consider large initial data f in for the Boltzmann equation, and thus large (ρ 0 in , u 0 in , θ 0 in ) for the Navier-Stokes-Fourier system, and in particular, showed that the solution f ε to (1.14) does not blow up before f 0 does.…”
mentioning
confidence: 99%
See 1 more Smart Citation